IMPLEMENTASI LEARNING MANAGEMENT SYSTEM SEBAGAI UPAYA MENINGKATKAN KREATIVITAS BELAJAR MAHASIWA PADA MATA KULIAH PAI DI STIT MUHAMMADIYAH BANGIL - Rizki Ghonia Rahma; Iwantoro Iwantoro (JIE (Journal of Islamic Education), 2020)
Education is a very important thing in life. In order to increase the learning creativity of STIT Muhammadiyah Bangil students, the efforts of lecturers, especially here, are the efforts of Islamic Education lecturers in online learning. The method used by researchers is a qualitative method that is descriptive of the data generated through interviews and documentation. The results of this study include the type of Learning Management System used by STIT Muhammadiyah Bangil lecturers in e-learning activities using unpaid applications such as Edmodo and Google Classroom, the implementation of the use of e-learning as an effort to increase student learning creativity in the Islamic Religious Education course. Is to maximize procedures and applications in the implementation of online learning. The challenges faced and opportunities found in the implementation of e-learning are the challenges of lecturers and students in learning that take place must communicate well and synergize with each other because learning is not seen directly, while the opportunities make it easier for students and lecturers to interact with each other to discuss material or lessons where course, easier access, and understand students to be technology literate.